2018
DOI: 10.4103/jfmpc.jfmpc_180_17
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound identification of fetal gender at the gestational age of 11–12 weeks

Abstract: Introduction:The early prenatal identification of fetal gender is of great importance. Accurate prenatal identification is currently only possible through invasive procedures. The present study was conducted to determine the accuracy and sensitivity of ultrasound fetal gender identification.Materials and Methods:The present cross-sectional study was conducted on 150 women in their 11th and 12th weeks of pregnancy in Hamadan in 2014. Ultrasound imaging performed in the 11th and 12th weeks of pregnancy for fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
2
3
0
Order By: Relevance
“…Though the accuracy of this method may not be determined, it is non-invasive, no associated risk, no cost involved and it may reduce selective abortion. Thus we agree with [11], that prenatal sex determination has high accuracy in invisible procedures compared to other methods. This also agrees with other studies which found that women avoid some methods of contraception that are believed to interfere with foetal positions [15]…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though the accuracy of this method may not be determined, it is non-invasive, no associated risk, no cost involved and it may reduce selective abortion. Thus we agree with [11], that prenatal sex determination has high accuracy in invisible procedures compared to other methods. This also agrees with other studies which found that women avoid some methods of contraception that are believed to interfere with foetal positions [15]…”
Section: Discussionsupporting
confidence: 90%
“…It is of great importance to know the sex of baby before birth [11]. Though, some of the pregnant women may need to know the sex of the baby due to curiosity, majority need to know the foetal sex as a measure to prepare for its birth by purchasing the requirement for the baby based on the identified sex [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao et al 18 also show higher sensitivity of detecting the male gender. Similar results have been reported by Perri et al 20 Gharekhanloo et al 9 and Efrat et al 11 also showed a higher sensitivity of detecting the female gender in their studies.…”
Section: Discussionsupporting
confidence: 89%
“…In males, penis, and scrotal sacs with or without testes are demonstrated. The female foetuses reveal the absence of male organs; with better and newer equipment also demonstrating vulva, clitoris, and labia 9 . P J M H S Vol.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 57 male fetuses were correctly identified as boys, and 8 female fetuses were wrongly identified as boys. The positive predictive value for the ultrasound imaging gender identification was 87.6% for the male fetuses and 96.8% for female fetuses (14).…”
Section: Discussionmentioning
confidence: 92%